Structural, genomic information and computational analysis of emerging coronavirus (SARS-CoV-2) - Agarwal, Deepak (2023)
Ongoing pandemic outbreaks (COVID-19) and public health crises were intimidating across the globe with the appearance and spread of the 2019 novel coronavirus known as SARS-CoV-2. SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) quickly spread from its origin in the Wuhan City of Hubei Province of the Republic of China, a country in East Asia, to the rest of the world (Wang et al. 2020a, b). Still, with small amounts of asymptomatic transmission between people, it spreads throughout the globe (Mohan et al. 2021). Coronaviruses (CoVs) are single-stranded, large, enveloped RNA viruses. They are spherical pleomorphic particles with bulbous surface projections. The CoVs genome size is from 29.8 to 29.9 kb (Su et al. 2016; Zheng et al. 2020). Virus particles have an average diameter of 12 μm (120 nm), an average envelope diameter of 0.08 μm (~ 80 nm), and spike length is 0.02 μm (~ 20 nm). The electron micrograph shows dense shells of an envelope with distinct electron pairs (Fehr and Perlman 2015).